Advanced Adaptive PID Controller for BLDC Motor - Mahmud, Md; Motakabber, S. M. A.; Islam, A. H. M. Zahirul; Nordin, Anis Nurashikin; Fawwaz Wafa, S. A. (IEEE, 2021)
Brushless DC (BLDC) motors are very popular for applications in automation and electric vehicle systems due to their unique features. Although these motors have many advantages over conventional DC motors, they also suffer some limitations in their functionality due to their direct dependability on the controller driver circuit. The proportional integral derivative (PID) controller is a common and widely used control system in the BLDC motors and various applications. However, this simple system is insufficient to manage the BLDC motors’ precise control in variable load, speed, and driving voltage. An auto-tuner can be used with a PID controller to increase the system adaptation. The proposed adaptive PID controller would quickly control the BLDC motors with minimal adjustment time and oscillation. The proposed controller system has been designed using mathematical transfer function modelling and verified by simulation using MATLAB software. Preliminary results showed that the overall ripple is less than 1% and has a faster stabilization time, which is better than other controllers